Transcribing Genes the Hard Way: In Vitro Reconstitution of Nanoarchaeal RNA Polymerase Reveals Unusual Active Site Properties - Nottebaum, Sven; Weinzierl, Robert O. J. (Frontiers in Molecular Biosciences, 2021)
Nanoarchaea represent a highly diverged archaeal phylum that displays many unusual biological features. The Nanoarchaeum equitans genome encodes a complete set of RNA polymerase (RNAP) subunits and basal factors. Several of the standard motifs in the active center contain radical substitutions that are normally expected to render the polymerase catalytically inactive. Here we show that, despite these unusual features, a RNAP reconstituted from recombinant Nanoarchaeum subunits is transcriptionally active. Using a sparse-matrix high-throughput screening method we identified an atypical stringent requirement for fluoride ions to maximize its activity under in vitro transcription conditions.